A phenomenological study on the set-up of three home offices belonging to three middle-income families residing in Quezon City - Libantino, Lou Ellen T.
This phenomenological study was conducted to analyze how selected home offices in Quezon City are set-up in terms of the design considerations used by the families and their location and lay-out within the residence. Using purposive sampling, the study included three residences with different types of home offices belonging to the middle-income families living within Quezon City. The data gathered was accomplished through questionnaires, interviews, measurements of the houses, and observation through photographs. The data obtained was analyzed by applying the Theory of Proxemics. Results and findings revealed that the main reason behind why the three families set up their business/office within the home is because they want to spend more time with their families. Aside from closeness to other family members, the other advantages of having a home office set-up as indicated by the data gathered are as follows: 1) saving on travelling time and gasoline; and 2) cost-effectiveness in terms of office rental fees. However, the findings showed that the home office set-up also has its drawbacks. Many of the users experience privacy problems and other distractions brought by the physical presence of an office within the house. Moreover, the lack of time boundaries between work and domestic activities pose conflicts among family members. These problems occur to some of the users because their workspaces are not separated from the family areas in the house. This study, therefore, recommends that the home office and family areas should be distinct and well-delineated as this will organize the business and domestic activities of the family members. Family relationships as well as business operations may be enhanced when the home office and areas specifically designed for family interaction are segregated and well-defined.